Perspectives on suicide - Seferović, Jelena (Prispevki za novejšo zgodovino, 2024)
The phenomenon of suicide is a profoundly intricate topic, influenced by a myriad of factors encompassing biological, biochemical, cultural, sociological, interpersonal, psychological, philosophical, conscious, and unconscious components. The examination of press publications, patient records from Croatian psychiatric institutions, and scholarly discourse on suicide in medical literature dating back to the late 19th and the early 20th century reveals that among the diverse perspectives of journalists and psychiatrists of that era, there are notable variations in terms of defining the reasons for suicide attempts. The absence of consistent explanations underscores the enigmatic nature of the ultimate resolution end one’s life. Although numerous experts and laypeople have claimed to know the exact motives behind someone resorting to suicide, some have continued to look for an explanation in otherworldly forces or individuals with supernatural powers. In essence, the multifaceted nature of suicide necessitates a nuanced and comprehensive approach, integrating various disciplines and perspectives to attain a deeper understanding of this phenomenon.
Keywords: 19. st.; 20. st.; BiH; Bosna in Hercegovina; Croatia; history; Hrvaška; jugoslavija; samomori; suicide; zgodovina